College students' interpretations of food security questions: results from cognitive interviews - Cassandra J. Nikolaus; Brenna Ellison; Sharon M. Nickols-Richardson (BMC, 2019)
Abstract Background Food insecurity (FI) - the lack of sufficient access to food to maintain a healthy lifestyle - among college (i.e. post-secondary or higher education institution) students has become a prominent issue in the U.S. However, it is not clear if high rates of FI among students are due to the modern experience in higher education institutions or due to underlying issues in common surveying methods. To understand if there were underlying content validity issues, the present study had two primary research questions: 1) How do students interpret the U.S. Department of Agriculture (USDA) Food Security Survey Module (FSSM) questionnaire items, and 2) How do responses of students experiencing FI compare with the theorized experiences and coping responses? Methods Thirty-three undergraduate students, aged 18- to 24-years old and fluent in English were recruited from a single 4-year university. During a 60-min session, participants completed the 10-item Adult FSSM and then were cognitively interviewed about their responses using the think-aloud method. Interview transcripts were analysed by two researchers using a collaborative process and basic interpretative approach. Results Students were on average 19.5 years old (± 1.2 years), the majority were in their freshman or sophomore (i.e., first or second) year, and 67% (n = 22) experienced FI. Results indicated that students' interpretations of key terms - such as "money for more," "balanced meals," and "real hunger" - diverge from expectations. Furthermore, students categorized as food insecure reported experiences and responses to FI that varied from theoretical dimensions of the process. Conclusions Though limited by sample size and representativeness, the present results indicate that the content validity of the FSSM may be compromised in this population and the managed process of FI may present differently among college students. Further psychometric research on modifications to the FSSM or with new FI assessment tools should be conducted with college students.